2019
DOI: 10.1177/0300060519893858
|View full text |Cite
|
Sign up to set email alerts
|

Levels of soluble cell adhesion molecules in type 2 diabetes mellitus patients with macrovascular complications

Abstract: Objective Type 2 diabetes mellitus (T2DM) is a main risk factor for development of cardiovascular diseases (CVDs) and endothelial dysfunction. This study aimed to investigate serum levels of soluble vascular cell adhesion molecule 1 (sVCAM-1), intercellular adhesion molecule 1 (sICAM-1), and endothelium selectin (sE-selectin) in T2DM patients with macrovascular complications. Methods A cross-sectional study of 21 controls, 30 T2DM patients without CVDs, and 30 T2DM patients with CVDs was conducted. Serum level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…It was observed in the present study that hsCRP and sICAM-1 levels were elevated in diabetic patients compared to healthy volunteers, which are following previous studies that demonstrated the increased level of these markers in diabetic patients and their association with future diabetic complications and mortality [20,23]. At the current work, a statistically significant reduction in hsCRP levels in the intervention group was found following randomized controlled trials which demonstrated the beneficial effect of NS on the CRP level of patients with different disease states [34].…”
Section: Similarly With Regards To Cell Adhesion Molecules a Linear Association Was Reported Between Elevations Of Icam-1 And Diabetic Resupporting
confidence: 89%
See 1 more Smart Citation
“…It was observed in the present study that hsCRP and sICAM-1 levels were elevated in diabetic patients compared to healthy volunteers, which are following previous studies that demonstrated the increased level of these markers in diabetic patients and their association with future diabetic complications and mortality [20,23]. At the current work, a statistically significant reduction in hsCRP levels in the intervention group was found following randomized controlled trials which demonstrated the beneficial effect of NS on the CRP level of patients with different disease states [34].…”
Section: Similarly With Regards To Cell Adhesion Molecules a Linear Association Was Reported Between Elevations Of Icam-1 And Diabetic Resupporting
confidence: 89%
“…There is also a link between the levels of ICAM-1 and diabetic neuropathy [22]. So, both CRP and soluble adhesion molecules can be considered as attractive early predictors of diabetic complications and therapeutic targets for diabetic patients [23].…”
Section: Similarly With Regards To Cell Adhesion Molecules a Linear Association Was Reported Between Elevations Of Icam-1 And Diabetic Rementioning
confidence: 99%
“… 1 Kingdom of Saudi Arabia (KSA) has the second-highest rate of T2DM prevalence in the Middle East. 2 The inflammatory process is one of the T2DM pathophysiological mechanisms. Throughout glycemic control deterioration, various factors affect the endothelium leading to endothelial dysfunction that deteriorates with insulin resistance (IR); these conditions are associated with T2DM macrovascular complications (MVC).…”
mentioning
confidence: 99%
“…The functional enrichment analysis indicated that the DEGs were primarily involved in the defense response, secretory vesicle, identical protein binding, cell adhesion, extracellular matrix, structural molecule activity, neutrophil degranulation and extracellular matrix organization. Neutrophil degranulation [52], innate immune system [53], platelet degranulation [54], extracellular matrix organization [55], diseases of glycosylation [56], platelet activation, signaling and aggregation [57], hemostasis [58], secretion [59], secretory vesicle [60], transmembrane transporter activity [61], cell adhesion [62], localization of cell [63], extracellular matrix [55], intrinsic component of plasma membrane [64], structural molecule activity [65], signaling receptor binding [66], have been highly noted in T2DM. Reports indicate that HIF1A [67], HLA-DRB1 [68], CHI3L1 [69], ADORA2A [70], ADRB2 [71], CLU (clusterin) [72], AGT (angiotensinogen) [73], VCAM1 [74], PPARA (peroxisome proliferator activated receptor alpha) [75], APOL1 [76], ZFP36 [77], PPM1B [78], SOCS1 [79], SNCA (synuclein alpha) [80], CTSS (cathepsin S) [81], IL6R [82], CFB (complement factor B) [83], DEFB1 [84], VNN1 [85], RAB27A [86], DPP4 [87], RARRES2 [88], CASP1 [89], LCN2 [90], REG3A [91], CD74 [92], PCSK2 [93], CHGB (chromogranin B) [94], TTR (transthyretin) [95], LRG1 [96], ALB (albumin) [97], DPP7 [98], APOH (apolipoprotein H) [99], CTSD (cathepsin D) [100], GCG (glucagon) [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 […”
Section: Discussionmentioning
confidence: 99%